MDMA-facilitated cognitive-behavioural conjoint therapy for posttraumatic stress disorder: an uncontrolled trial. Issue 1 (31st December 2020) - Monson, Candice M.; Wagner, Anne C.; Mithoefer, Ann T.; Liebman, Rachel E.; Feduccia, Allison A.; Jerome, Lisa; Yazar-Klosinski, Berra; Emerson, Amy; Doblin, Rick; Mithoefer, Michael C.
ABSTRACT: Cognitive-behavioural conjoint therapy (CBCT) for PTSD has been shown to improve PTSD, relationship adjustment, and the health and well-being of partners. MDMA (3, 4-methylenedioxymethamphetamine) has been used to facilitate an individual therapy for PTSD. This study was an initial test of the safety, tolerability, and efficacy of MDMA-facilitated CBCT. Six couples with varying levels of baseline relationship satisfaction in which one partner was diagnosed with PTSD participated in a condensed version of the 15-session CBCT protocol delivered over 7 weeks. There were two sessions in which both members of the couple were administered MDMA. All couples completed the treatment protocol, and there were no serious adverse events in either partner. There were significant improvements in clinician-assessed, patient-rated, and partner-rated PTSD symptoms (pre- to post-treatment/follow-up effect sizes ranged from d = 1.85–3.59), as well as patient depression, sleep, emotion regulation, and trauma-related beliefs. In addition, there were significant improvements in patient and partner-rated relationship adjustment and happiness ( d =.64–2.79). These results are contextualized in relation to prior results from individual MDMA-facilitated psychotherapy and CBCT for PTSD alone. MDMA holds promise as a facilitator of CBCT to achieve more robust and broad effects on individual and relational functioning in those with PTSD and their partners. Abstract : HIGHLIGHTS: MDMA was combined with cognitive-behavioural conjoint therapy for PTSD in six couples revealing significant improvements in PTSD, depression, sleep, emotion regulation, trauma beliefs, and relationship satisfaction. Controlled studies are planned based on these promising results.